The Phenomenon of Market Distortion Practices in E-Commerce (Bai' Najasy) - Agustin Mila Arlina; Lilik Rahmawati; Ahmad Agus Hidayat (University of Darussalam Gontor, 2023)
E-commerce is one of the marketing technologies used as a platform for online buying and selling in the present time. However, in its mechanism, there are similarities with the practice of Market Distortion (bai' najasy) in e-commerce, which is prohibited in Islam. This research aims to understand the practice of Market Distortion (bai' najasy) in e-commerce from the perspective of Islamic economics. This study uses a qualitative descriptive method by conducting direct research on the target audience. It is known that the phenomenon of market distortion (Ba'i Najasy) among e-commerce users in the Tanjung Village, Kedamean Subdistrict, Gresik Regency, still frequently occurs due to consumers being less selective and hasty in choosing a seller for a product. Based on interviews conducted by the researcher with 100 respondents representing the target audience, it was found that 67 of them expressed dissatisfaction with products purchased through e-commerce applications, while 17 others stated that they had been satisfied with their initial purchase but were less satisfied with their second purchase, and 16 others had not experienced what the other respondents had. This indicates the need for education among the public to selectively choose sellers on e-commerce applications.